PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PELAYANAN APARAT KECAMATAN (STUDI KASUS PADA KANTOR KECAMATAN BATULAPPA) - Supratman; Arfianty (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of motivation and work discipline on the service of the Kecamatan Batulappa, Kabupaten Pinrang. This research uses quantitative methods. The sample used was 22 respondents. Verify instruments with validity and reliability tests. The analysis method was statistical using the software tool of SPSS (Statistical Package for Social Science) version 25. The results study show that the incentive to work on equipment services in Kecamatan Batulappa, Kabupaten Pinrang has a majority positive impact. Besides, job discipline also has, but not substantially, a positive effect on the servicing of officers in Kecamatan Batulappa, Kabupaten Pinrang. The two variables have a majority positive influence at the same time.